2016
DOI: 10.1111/ejn.13352
|View full text |Cite
|
Sign up to set email alerts
|

Blocking transient receptor potential vanilloid 2 channel in astrocytes enhances astrocyte‐mediated neuroprotection after oxygen–glucose deprivation and reoxygenation

Abstract: Astrocytes play important roles in homeostatic regulation in the central nervous system and are reported to influence the outcome of ischemic injury. Regulating Ca signaling of astrocytes is a promising strategy for stroke therapy. Herein, we report for the first time that transient receptor potential vanilloid 2 (TRPV2), a Ca -permeable channel that is important in osmotic balance regulation, expresses in rat cortical astrocytes by immunofluorescence. Moreover, oxygen-glucose deprivation and reoxygenation (OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Along this line, the present study showed that PACA effectively preserved the activation of PI3K/Akt, ERK1/2 CREB, and TrkA signaling pathways and maintained the levels of NGF protein in MPTP-treated mice. A recent study suggested that astrocytes produced NGF to support the survival of neurons against oxidative stress [44,45]. Consistently, the present study also showed that PACA might induce NGF expression in the entire midbrain cell population including astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Along this line, the present study showed that PACA effectively preserved the activation of PI3K/Akt, ERK1/2 CREB, and TrkA signaling pathways and maintained the levels of NGF protein in MPTP-treated mice. A recent study suggested that astrocytes produced NGF to support the survival of neurons against oxidative stress [44,45]. Consistently, the present study also showed that PACA might induce NGF expression in the entire midbrain cell population including astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…For example, of the small calcitonin gene-related peptide (CGRP) +ve neurons projecting to the skin, 11.6% were positive for TRPV2. Involvement of TRPV2 in neuro-protection have also been reported [55]. Here we demonstrate that TRPV2 plays important role in the regulation of neuritogenesis process.…”
Section: Discussionsupporting
confidence: 80%
“…For example, of the small CGRP +ve neurons projecting to the skin, 11.6% were positive for TRPV2. Involvement of TRPV2 in neuro-protection have also been reported 56 . Here we demonstrate that TRPV2 plays important role in the regulation of neuritogenesis process.…”
Section: Discussionmentioning
confidence: 88%